Synthetic Studies on Cyclocitrinol: Construction of the ABC Ring System Based on Epoxy–Nitrile Cyclization - Sato, Kazuto; Tanino, Keiji (Synlett, 2021)
The stereoselective synthesis of a model compound containing the ABC ring system of cyclocitrinol was accomplished. After connecting a C ring allyltitanium segment with an A ring bicyclo[4.1.0]heptanone segment, the seven-membered B ring moiety was constructed by an intramolecular cyclization reaction of an epoxy nitrile. The enone moiety was introduced through an oxidative decyanation reaction, and the bicyclo[4.4.1]undecane skeleton with the highly strained olefin moiety was formed through a ring-opening reaction of the bicyclo[4.1.0]heptane substructure.
Keywords: natural product; total synthesis; allyl titanocene; epoxy nitrile; cyclization reaction; cyclopropane ring opening; cyclocitrinol